Impact of climate change on small ruminants production: A review - Biswal, Jyotsnarani; Kennady, Vijayalakshmy; Rahman, Habibar (Crimson Publishers, 2021)
Sheep and goats, known as small ruminants, are an important component group of livestock, representing 58% of the global domestic ruminant population. Both sheep and goats are adapted well under varied climatic conditions including harsh climates. The large-scale presence of these animals in the arid regions indicates the adaptability of these animals to the hotter climatic conditions. the impact of climate change and consequential heat stress conditions, however, has been found to affect the growth and production, milk yield, feed intake, reproductive performance, and other biological functions of these animals. Through the present paper, an effort has been made to review the impact of the elevated environmental temperatures on the production performance of sheep and goats and provide certain alleviation strategies to overcome the climatic extremes.